RETRACTED: Relationship between Carotid Body Tumor and Thyroid Papillary Cancer - Demirag Evman, Melis; Atalay Erdogan, Banu (ENT Updates, 2025)
The article titled “Relationship between Carotid Body Tumor and Thyroid Papillary Cancer” has been formally retracted. Following its publication, the publisher received a complaint indicating that the article had significant problems regarding the accuracy of the reported clinical case details and inconsistencies in author contribution attribution. In accordance with our complaints procedure, the editorial office and the Editorial Board conducted an investigation, which confirmed that these problems make the research results unreliable. Consequently, the Editorial Board has decided to retract the article. This retraction has been approved by the Editor-in-Chief of ENT Updates. All authors have agreed to the retraction. Retraction Date: 5 December 2025 This is a notice of retraction for the article with DOI: https://doi.org/10.54963/entu.v15i4.2020